Measuring Healthiness Of Islamic Banks Using Solvabilitas Financial Ratios - Muhammad Hanafi Zuardi (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2021)
The purpose of the study was to analyze the soundness level of PT Bank Central Asia (BCA) Syariah using the solvency ratio for the 2015-2019 period. This type of research is quantitative with a descriptive approach, where the data source used is secondary data sources. The data collection technique uses the documentation method in the form of financial reports which have been presented on the official website of PT BCA Syariah. The data analysis technique uses the assessment of the level of health using the solvency ratio with independent variables and measurement using the CAR and DER ratios. The results showed that the CAR ratio for the 2015-2019 period was ranked 1 in the very healthy category, namely the CAR ratio was greater than the predetermined bank health standard, namely 8%. Meanwhile, the DER ratio for the 2015-2019 period experienced a significant increase. This increase in the DER ratio indicates that the condition of the DER ratio is in an unhealthy state, because the calculation of the DER ratio is more than the minimum health standard for the DER ratio, namely DER <58%. Based on the results of the study, the health composite ranking of PT BCA Syariah using the Solvency Ratio in 2015-2019 The CAR ratio is in a healthy rating, while the DER ratio is in a very unhealthy rating. so this indicates that the bank has not been able to finance its long-term and short-term debt with its own capital.